Analisis Faktor Penyebab dan Dampak Kualitas Belajar Mahasiswa Berbasis Daring di Masa Pandemi Covid-19 - Wayan Supada; Gusti Ayu Putu Diah Permata Sari; I Gede Teguh Heriawan; I Gede Titah Pratyaksa (Jayapangus Press, 2021)
The e-learning system can create individuation, enrichment, acceleration, expansion, productivity and effectiveness in learning so that the quality of education can increase during the Covid-19 pandemic. This research was conducted to find the right formulation of the online lecture system in the future. In this study, the research population was all students of the communication science study program, totaling 259 people. For the needs of analysis and hypothesis testing, the entire population is used as the research sample. So the research is included in population research. The analytical technique used in this study uses a structural equation model (SEM) with the AMOS 21.0 program which consists of several stages. The results showed that of the nine paths and hypotheses built, seven hypotheses had a positive and significant effect, while two hypotheses had an insignificant effect.